New trends in fuzzy logic proceedings of the WILF '95, Italian Workshop on Fuzzy Logic, Naples, Italy, 21-22 September 1995 - Bonarini, Andrea (World Scientific, 1996)
"This book reports the recent results obtained by Italian researchers in fuzzy logic. It collects some selected papers presented at the 1995 Italian Workshop on Fuzzy Logic (WILF'95), and some invited contributions. The book covers some of the most interesting topics in fuzzy logic: theory, evolutionary computing, and gives an overview of applications in control, image processing, pattern recognition, decisions support systems, and high energy physics."--